The Phrenological journal and science of health ... incorporated with the Phrenological magazine ... Devoted to ethnology, physiology, phrenology, physiognomy, sociology, psychology, education, mechanical industry, hygiene, and to all those progressive measures which are calculated to reform, elevate, and improve mankind, spiritually, intellectually, and socially. - Allen, Nathan 1813-1889; Beall, Edgar Charles 1853-; Drayton, Henry Shipman 1840-; Fowler, Lorenzo Niles 1811-1896; Fowler, Orson Squire 1809-1887; Sizer, Nelson 1812-1897; Wells, Samuel Robert 1820-1875 (O.s. & L.N. Fowler, 1838)
Monthly.